Characterization of the early gene expression profile in Populus ussuriensis under cold stress using PacBio SMRT sequencing integrated with RNA-seq reads. (9th October 2021) - Li, Wenlong; Fu, Yanrui; Lv, Wanqiu; Zhao, Shicheng; Feng, He; Shao, Liying; Li, Chenghao; Yang, Jingli
Abstract: Populus ussuriensis is an important and fast-growing afforestation plant species in north-eastern China. The whole-genome sequencing of P. ussuriensis has not been completed. Also, the transcriptional network of P. ussuriensis response to cold stress remains unknown. To unravel the early response of P. ussuriensis to chilling (3 °C) stress and freezing (−3 °C) stresses at the transcriptional level, we performed single-molecule real-time (SMRT) and Illumina RNA sequencing for P. ussuriensis . The SMRT long-read isoform sequencing led to the identification of 29, 243, 277 subreads and 575, 481 circular consensus sequencing reads. Approximately 50, 910 high-quality isoforms were generated, and 2272 simple sequence repeats and 8086 long non-coding RNAs were identified. The Ca 2+ content and abscisic acid (ABA) content in P. ussuriensis were significantly increased under cold stresses, while the value in the freezing stress treatment group was significantly higher than the chilling stress treatment group. A total of 49 genes that are involved in the signal transduction pathways related to perception and transmission of cold stress signals, such as the Ca 2+ signaling pathway, ABA signaling pathway and MAPK signaling cascade, were found to be differentially expressed. In addition, 158 transcription factors from 21 different families, such as MYB, WRKY and AP2/ERF, were differentially expressed during chilling and freezing treatments. Moreover, the measurement of physiological indicators and bioinformatics observations demonstrated the altered expression pattern of genes involved in reactive oxygen species balance and the sugar metabolism pathway during chilling and freezing stresses. This is the first report of the early responses of P. ussuriensis to cold stress, which lays the foundation for future studies on the regulatory mechanisms in cold-stress response. In addition the full-length reference transcriptome of P. ussuriensis deciphered could be used in future studies on P. ussuriensis .